2018
DOI: 10.1177/1069072718758064
|View full text |Cite
|
Sign up to set email alerts
|

Access to Decent and Meaningful Work in a Sexual Minority Population

Abstract: People who identify as sexual minorities consistently face barriers to decent and meaningful employment, especially when coupled with additional constraints such as low socioeconomic status or marginalization experiences. Drawing from the psychology of working theory as our theoretical framework, this study examined the relations of economic constraints (social class) and marginalization (negative sexual minority workplace climate) to work volition, decent work, and meaningful work with a sample of working adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 57 publications
(76 reference statements)
5
71
1
1
Order By: Relevance
“…Although we view decent work as a key predecessor of meaningful work, some individuals may have the capacity to experience their work as meaningful even if it is not decent. For example, correlations between decent work and meaningful work are strong but range from 0.48-0.58 (Allan, Tebbe, Bouchard, & Duffy, 2018;Duffy et al, 2017;Işık, Kozan, & Işık, 2018), indicating these are not completely overlapping constructsit is possible to have one without the other. To date, however, it is unclear what types of individuals would be more likely to experience meaningful work in environments where one or more components of decent work is absent.…”
Section: Access To Decent Workmentioning
confidence: 99%
“…Although we view decent work as a key predecessor of meaningful work, some individuals may have the capacity to experience their work as meaningful even if it is not decent. For example, correlations between decent work and meaningful work are strong but range from 0.48-0.58 (Allan, Tebbe, Bouchard, & Duffy, 2018;Duffy et al, 2017;Işık, Kozan, & Işık, 2018), indicating these are not completely overlapping constructsit is possible to have one without the other. To date, however, it is unclear what types of individuals would be more likely to experience meaningful work in environments where one or more components of decent work is absent.…”
Section: Access To Decent Workmentioning
confidence: 99%
“…Another trend that is changing the occupational landscape has been the growth of economic inequality, which has been increasing in many nations since the early 1970s (Stiglitz, 2015). The rise of inequality is creating a world where opportunity to thrive, via work and other agentic efforts in creating a good life, is limited by one's social class, gender, race, and access to social and human capital (Ali, 2013;Allan, Tebbe, Bouchard, & Duffy, 2018;Flores, 2013). In our view, the gradual diminishment of equal access to decent work and the rise in inequality are striking aspects of the contemporary labor market, which clearly compromises the potential for fully realized human rights at work.…”
Section: Unemployment the Rise Of Precarious Work And Inequalitymentioning
confidence: 99%
“…In contrast, the hypothesized effect of proactive personality as a moderator within a PWT model has been rejected (Douglass et al, 2019). Recent research has identified additional predictors of decent work within a PWT frame, including working women’s sense of workplace climate (e.g., respect; England et al, 2020), LGBTQ+ workers’ workplace climate (Allan et al, 2019), and psychological ownership of their jobs (Smith et al, 2020).…”
Section: Psychology Of Working Theory and Decent Workmentioning
confidence: 99%
“…Other research affirmed decent work as a predictor of survival, social contribution, and self-determination needs, and moreover, a predictor of physical health and mental health, indirectly via needs satisfaction (Duffy, Kim, et al, 2019). As specified in PWT, decent work has been found to predict meaningful work (Allan et al, 2019). Uniformity of decent work between jobs and workplaces cannot be assumed, that is, the levels of each element of decent work may vary in different contexts.…”
Section: Psychology Of Working Theory and Decent Workmentioning
confidence: 99%